2019
DOI: 10.3390/pathogens8020079
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Identification of Virulence, Antimicrobial and Heavy Metal Resistance Genes in Livestock-Associated Methicillin-Resistant Staphylococcus aureus

Abstract: Staphylococcus aureus is one of the most important pathogens of humans and animals. Livestock production contributes a significant proportion to the South African Gross Domestic Product. Consequently, the aim of this study was to determine for the first time the prevalence, virulence, antibiotic and heavy metal resistance in livestock-associated S. aureus isolated from South African livestock production systems. Microbial phenotypic methods were used to detect the presence of antibiotic and heavy metal resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 89 publications
9
37
0
Order By: Relevance
“…In the present work, copper-tolerant A. baumannii could be detected in both clinical and natural environmental isolates. Previous studies reported that copper tolerance was found in pathogenic bacteria isolated from environmental, food, and clinical samples [11,31,32]. We found a narrow range of copper MIC values (5 and 10 mM) for 407 A. baumannii isolates, by using a rich growth medium (MHA).…”
Section: Discussionmentioning
confidence: 82%
“…In the present work, copper-tolerant A. baumannii could be detected in both clinical and natural environmental isolates. Previous studies reported that copper tolerance was found in pathogenic bacteria isolated from environmental, food, and clinical samples [11,31,32]. We found a narrow range of copper MIC values (5 and 10 mM) for 407 A. baumannii isolates, by using a rich growth medium (MHA).…”
Section: Discussionmentioning
confidence: 82%
“…aureus has been considered as the most common causative pathogen in surgical site infections in recent years [13]. The ability of S. aureus to infect humans and animals poses a huge burden on the healthcare system [14]. Molecular typing methods such as pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), and Staphylococcus protein A (spa) typing have been widely used to track the sources and transmissions of pathogenic bacteria like S. aureus, thereby helping to establish the national and global epidemiological data [3].…”
Section: Introductionmentioning
confidence: 99%
“…If there will be no corresponding policy formulation, the global consumption of antibiotics in 2030 would be up to 200% higher than in 2015 [15]. However, a major cause for alarm is the drastic rise of antibiotic resistance of S. aureus with the increase in the use of antibiotics [14]. The World Health Organization (WHO) has identified antibiotic resistance as one of the biggest challenges to global health and classified S. aureus as a high priority superbug for which research and development of novel antibiotics are needed urgently [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Switzerland, the pathogen was isolated from only 1 % of calves and 0.3 % of adult cattle [16], whereas in Denmark, the rate exceeds 64% in goats [17]. Moreover, a recent study conducted by Dweba et al [19], in South African livestock production systems identified MRSA isolates in 27% with a significant relationship (p < 0.001) with the host animal.…”
Section: Discussionmentioning
confidence: 99%